The role of predevelopment activities and firm attributes in new product success - Murphy, Steven A.; Kumar, Vinod
The authors consider the stages of predevelopment of new products, a hitherto relatively unresearched field. Fifteen firms in the printed circuit board industry were studied in relation to new product success.
The product development literature focuses largely on improving the efficiency and success rates of the development process, while largely neglecting the activities that comprise the predevelopment stages. The result is that little is known about how or why predevelopment practices differ among firms. Our study of fifteen firms in Ontario's integrated circuit board industry revealed interesting differences in predevelopment practices that directly affected the likelihood of new product success. It was revealed that firm size, age, and R&D intensity were significant predictors of predevelopment practices. In addition, activities were identified that serve as a prescriptive guide for the successful development and market launch of new products.
Keywords: Predevelopment activities; Firm attributes; Product success